Electrically actuated visible and near-infrared regulating switchable smart window for energy positive building: A review. (10th June 2021) - Nundy, Srijita; Mesloub, Abdelhakim; Alsolami, Badr M.; Ghosh, Aritra
Abstract: Building consumes fossil fuel generated electricity to satisfy its air condition, heating and artificial lighting load demand. Offsetting this building energy demand by employing energy efficient advanced switchable smart windows are possible. Currently, electrically actuated switchable smart window systems include electrochromic (EC), suspended particle device (SPD) and liquid crystal (LC). EC works under direct current (DC) power supply while SPD and LC need alternating current (AC) power supply. In this work, details (working principle, window parameters and building energy saving potential) of these three window technologies have been reviewed. Highly insulated switchable smart window and powering them employing PV system is also an attractive strategy. However, smart windows need stakeholder support particularly from government and building regulation code for its smooth penetration to the building sector.